Effect of carbon support on the activity of monodisperse Co45Pt55 nanoparticles for oxygen evolution in alkaline media - Andrić, Stevan; Milikić, Jadranka; Sevim, Melike; Santos, Diogo M. F.; Šljukić, Biljana (Frontiers in Chemistry, 2023)
Oxygen evolution reaction (OER) represents the efficiency-limiting reaction in water electrolyzers, metal-air batteries, and unitized regenerative fuel cells. To achieve high-efficiency OER in alkaline media, we fabricated three novel electrocatalysts by the assembly of as-prepared Co45Pt55 alloy nanoparticles (NPs) on three different carbon-based support materials: reduced graphene oxide (CoPt/rGO), mesoporous graphitic carbon nitride (CoPt/mpg-CN), and commercial carbon Ketjenblack carbon (CoPt/KB). Voltammetry studies revealed that CoPt/rGO electrocatalyst provided lower OER overpotentials accompanied by higher currents and specific current density values than the other two studied materials. Moreover, CoPt/rGO outperformed commercial CoPt/C electrocatalysts in terms of notably higher specific current densities. Additionally, it was found that CoPt/rGO electrocatalyst activity increases with increasing temperature up to 85 °C, as suggested by the increase in the exchange current density. Electrochemical impedance spectroscopy studies of three electrocatalysts in OER revealed similar charge transfer resistance, although CoPt/rGO provided a higher current density. The main issue observed during long-term chronoamperometry and chronopotentiometry studies is the materials' instability under OER polarization conditions, which is still to be tackled in future work.